2020
DOI: 10.1002/aoc.5998
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, antimicrobial activity, 3D‐QSAR, DFT, and molecular docking of some ciprofloxacin derivatives and their copper(II) complexes

Abstract: Six new derivatives of ciprofloxacin compounds and their copper(II) complexes were synthesized, characterized by spectroscopic methods (ultraviolet–visible [UV–vis], Fourier transform infrared [FTIR], nuclear magnetic resonance [NMR], mass spectrometry [MS], and electron paramagnetic resonance [EPR]), and tested for antibacterial activities against gram‐negative and gram‐positive bacteria. The data showed that ciprofloxacin derivatives act as bidentate ligands and the metal ions coordinate through the pyridone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 46 publications
(41 reference statements)
0
16
0
Order By: Relevance
“…An early example from Aristilde et al discloses molecular dynamics (MD) simulations of ciprofloxacin in aqueous solvent and investigates the stability of complexes formed between ciprofloxacin and sodium, potassium, calcium, magnesium, and iron(II) [ 36 ]. Recent examples include DFT computations by Bridle et al modeling pH-dependent complexes of ciprofloxacin and magnesium in aqueous solution [ 37 ], and an experimental and computational study of ciprofloxacin derivatives complexed with copper(II) [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…An early example from Aristilde et al discloses molecular dynamics (MD) simulations of ciprofloxacin in aqueous solvent and investigates the stability of complexes formed between ciprofloxacin and sodium, potassium, calcium, magnesium, and iron(II) [ 36 ]. Recent examples include DFT computations by Bridle et al modeling pH-dependent complexes of ciprofloxacin and magnesium in aqueous solution [ 37 ], and an experimental and computational study of ciprofloxacin derivatives complexed with copper(II) [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that all synthesized hybrids are sensitive against the tested organism, and some of them are exhibited activity higher than the parent drug, ciprofloxacin. The compound 123 was the potent compound in this series and displayed antimicrobial activities against S. aureus, E. coli, and K. pneumonia with inhibition zone, 37, 40, and 11mm respectively higher than ciprofloxacin with inhibition zone, 21mm for all organism using Kirby-Bauer disk diffusion method [148].…”
Section: Antimicrobial Activitymentioning
confidence: 90%
“…The compound 38a almost inhibit the fungi about 73%. Сiprofloxacin (CF) derivatives HL 39 -HL 44 used for synthesis six copper complexes 39-44 general composition [Cu(L) 2 (H 2 O) x ]•yH 2 O [43]. CF belongs to class II of the second-generation fluoroquino-lone-synthetic antibiotics that are active against both Gram-positive and Gram-negative bacteria.…”
Section: N-donor Ligandsmentioning
confidence: 99%
“…(HL 39 ), p-methylphenyl (HL40 ), p-chlorolphenyl (HL41 ), p-nitrophenyl (HL42 ), furan (HL43 ), pyrrol (HL44 ) …”
mentioning
confidence: 99%